Eastern Han (AD 25-220) tombs in Sichuan - Chen, Xuan, 1985- (Archaeopress archaeology., 2015)
This work explores the many factors underlying the extended popularity of the cliff tomb, a local burial form in the Sichuan Basin in China during the Eastern Han dynasty (AD 25-220). The development of the cliff tomb was linked to a complex set of connections involved with burial forms, and continued through associations with many other contemporary burial practices: brick chamber tombs, stone chamber tombs, and princely rock-cut tombs. These connections and links formed to a large extent through the incorporation of the Sichuan region within the Empire, which began in the fourth century BC.